Guide to Computer Network Security - Kizza, Joseph Migga (Springer, 2017)
It has been barely 3 years since our third edition came out, and we are again in need of a new and improved fourth edition. This quick turnaround of editions of a successful book like this is indicative of the rapidly changing technology landscape. We are excited by our growing number of users, and we are indeed indebted to them by continuously keeping a living promise we first made to our readers in the very first edition of maintaining the book materials as up to date as possible. In line with this promise, we have now embarked on this fourth edition. Since our first edition, we have been bringing to our growing ranks of users not only the concept of a changing computer network but also the correspondingly evolving repertoire of security tools, algorithms, and best practices, all mandated by the rapidly changing technology. The traditional computer network we introduced in the first edition with its nicely “demarcated” and heavily defended perimeter wall and well-guarded access points has been going into a transformation as a result of new technologies. Changes have occurred, as we pointed out in both the second and third editions, from within and outside the network, at the server, and most importantly at the boundaries resulting into a virtualized and elastic network, with rapid extensions at will, to meet the growing needs of users. These changes are driven by new technological developments and changing user demands and security needs. New developments in system resource virtualization, the evolving cloud computing models, and a growing and unpredictable mobile computing technology are creating new platforms that demand new extensions, usually on the fly and at will, thus making security of the traditional computer network more complex.